2000
DOI: 10.1105/tpc.12.11.2247
|View full text |Cite
|
Sign up to set email alerts
|

SIMKK, a Mitogen-Activated Protein Kinase (MAPK) Kinase, Is a Specific Activator of the Salt Stress–Induced MAPK, SIMK

Abstract: In eukaryotes, mitogen-activated protein kinases (MAPKs) play key roles in the transmission of external signals, such as mitogens, hormones, and different stresses. MAPKs are activated by MAPK kinases through phosphorylation of MAPKs at both the threonine and tyrosine residues of the conserved TXY activation motif. In plants, several MAPKs are involved in signaling of hormones, stresses, cell cycle, and developmental cues. Recently, we showed that salt stressinduced MAPK (SIMK) is activated when alfalfa cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 167 publications
(76 citation statements)
references
References 60 publications
1
75
0
Order By: Relevance
“…Although alfalfa SIMK kinase (SIMKK) is considered as the specific activator of SIMK (Kiegerl et al 2000), direct evidence that link the SIMK downstream signaling with specific promoter activation or repression are still missing.…”
Section: Discussionmentioning
confidence: 99%
“…Although alfalfa SIMK kinase (SIMKK) is considered as the specific activator of SIMK (Kiegerl et al 2000), direct evidence that link the SIMK downstream signaling with specific promoter activation or repression are still missing.…”
Section: Discussionmentioning
confidence: 99%
“…LcMKK belongs to group A, which consists of several well-characterized MAPKK genes, including AtMKK2, NtSIMKK, and GhMKK1. It has been documented that MAPKK members in groups A are predominantly implicated in abiotic stress responses (Kiegerl et al 2000). Clustering of these genes in the same group suggested that they may have a similar or even the same biological functions in abiotic stress responses.…”
Section: Discussionmentioning
confidence: 99%
“…In Arabidopsis, AtMKK1 can activate AtMPK3 to transmit cold, salt, and drought signals (Mizoguchi et al 1998). In tobaccos, NtSIMKK can regulate salt stress signals by activating SIMK (Kiegerl et al 2000). NtMEK2 can activate WIPK and SIPK to transmit osmotic stress signals (Mikołajczyk et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…In general, MAPKKs are reported to be dual-speciWc kinases that phosphorylate threonine and tyrosine residues in the T-X-Y motif. In most cases, Thr alone or Thr and Tyr were shown to harbor the transferred phosphate group coinciding with the activation of plant MAPKs (Huang et al 2000;Kiegerl et al 2000;Nühse et al 2000). Huang et al (2000) concluded that AtMEK1 may not be a dual-speciWcity kinase.…”
Section: Figmentioning
confidence: 97%